2005
DOI: 10.1016/j.soilbio.2005.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Earthworms change the distribution and availability of phosphorous in organic substrates

Abstract: In laboratory controlled soil microcosms, the distribution and availability of phosphorous (P) were determined in the surface-casts and the burrows-linings of the anecic earthworm L. terrestris and were compared with non-ingested soil. To simulate more realistic earthworm community conditions, a combination of L. terrestris plus the endogeic A. caliginosa was tested. For a 2-month period, the earthworms were given two organic food substrates: rye-grass littered onto the soil surface and sewage sludge mixed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 15 publications
2
38
0
1
Order By: Relevance
“…Microbial activity is increased in the presence of earthworms, leading to nitrogen-mineralization and immobilization through direct or indirect benefits by earthworms 44 . Earthworms were also reported to increase the availability of phosphorus by facilitating changes in the biogeochemical status of P in burrow-linings 45 . In a pot experiment with earthworms, higher levels of plant available P resulted in increased plant growth from 15.7 to 16.8 g dry biomass per pot 46 .…”
Section: Nutrient Cycling In Soilmentioning
confidence: 99%
“…Microbial activity is increased in the presence of earthworms, leading to nitrogen-mineralization and immobilization through direct or indirect benefits by earthworms 44 . Earthworms were also reported to increase the availability of phosphorus by facilitating changes in the biogeochemical status of P in burrow-linings 45 . In a pot experiment with earthworms, higher levels of plant available P resulted in increased plant growth from 15.7 to 16.8 g dry biomass per pot 46 .…”
Section: Nutrient Cycling In Soilmentioning
confidence: 99%
“…3) (Zachmann et al, 1987;Kladivko et al, 1991;Roth et al, 1991;Flury, 1996;Mohanty et al, 1998;Stamm et al, 1998;Stamm et al, 2002). Earthworms are as classical ecosystem engineers of special interest in this context because they build long-lasting soil structures that exert a significant influence on water flows (Edwards et al, 1990b(Edwards et al, , 1992Smettem, 1992;Shipitalo and Butt, 1999) and solute transport (Edwards et al, 1993;Zehe and Flühler, 2001a, b;Domínguez et al, 2004;Alekseeva et al, 2006;Le Bayon and Binet, 2006) but also on organic matter dynamics, pedogenetic processes and plant growth (Lavelle et al, , 2004Hedde et al, 2005;Milcu, 2005;Milcu et al, 2006). However, whether or not connected structures are activated during a given rainfall event depends on the interplay of initial soil moisture and rainfall forcing.…”
Section: Infiltration and Vertical Preferential Flowmentioning
confidence: 99%
“…The higher levels of water-soluble inorganic P (C P ) in the termite nests presented in Table 8.1 may also result from the transformation of organic P through enzymatic activity in the fresh biostructures, as observed for earthworm casts (Sharpley and Syers 1976;Le Bayon and Binet 2006). Comparisons of phosphatase activities between termite nests and adjacent soils have already been made for several termite species (López-Hernández et al 1989b;Roose-Amsaleg et al 2005).…”
Section: Phosphorus Dynamics and Availability In Termite Moundsmentioning
confidence: 89%
“…The x-and y-axes are represented in log-log scales. Modified from Chapuis-Lardy et al (2009) studies reported increased enzymatic activity in earthworm casts and the stimulation of microbial activity (Sharpley and Syers 1976;James 1991;López-Hernández et al 1993;Chapuis and Brossard 1995;Brossard et al 1996;Le Bayon and Binet 2006). However, Zhang et al (2000) observed an increase of inorganic P in soils in the presence of earthworms, despite a decrease of acid and alkaline phosphatase activities in earthworm casts, suggesting that P-containing organic matter is digested in the gut rather than in the casts.…”
Section: Phosphorus Dynamics and Availability In Earthworm Castsmentioning
confidence: 99%